2013
DOI: 10.1007/978-3-319-02297-0_4
|View full text |Cite
|
Sign up to set email alerts
|

On Consistency of Finite Difference Approximations to the Navier-Stokes Equations

Abstract: Abstract. In the given paper, we confront three finite difference approximations to the Navier-Stokes equations for the two-dimensional viscous incomressible fluid flows. Two of these approximations were generated by the computer algebra assisted method proposed based on the finite volume method, numerical integration, and difference elimination. The third approximation was derived by the standard replacement of the temporal derivatives with the forward differences and the spatial derivatives with the central … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(56 citation statements)
references
References 20 publications
0
53
0
3
Order By: Relevance
“…(16) and (18) (19) and (21) give s-consistent FDA of the Navier-Stokes and pressure Poisson equations in the two-dimensional case as well. Examples of such FDA were studied in [6]. One more s-consistent two-dimensional FDA was derived in [7].…”
Section: Navier-stokes Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…(16) and (18) (19) and (21) give s-consistent FDA of the Navier-Stokes and pressure Poisson equations in the two-dimensional case as well. Examples of such FDA were studied in [6]. One more s-consistent two-dimensional FDA was derived in [7].…”
Section: Navier-stokes Equationsmentioning
confidence: 99%
“…In [4,5], for polynomially nonlinear PDE systems and regular solution grids, we introduced the novel concept of strong consistency, or s-consistency, which strengthens the concept of consistency and means that any element of the perfect difference ideal generated by the polynomials in FDA approximates an element in the radical differential ideal generated by the polynomials in PDE. In the subsequent papers [6,7], by computational experiments with two-dimensional incompressible Navier-Stokes equations, it was shown that s-consistent FDA have much better numerical behavior than FDA which are not s-consistent.…”
Section: Introductionmentioning
confidence: 99%
“…В работах [11,12] развит подход к построению разностных схем, основанный на построении пере-определенной системы разностных уравнений, получаемой из аппроксимации интегральных законов сохранения и интегральных соотношений, связывающих искомые функции и их производные. По-строение базиса Грёбнера соответствующих разностных многочленов позволяет построить разност-ную схему, которая автоматически обеспечивает выполнение интегральных законов сохранения по областям, составленным из шаблонов интегрирования.…”
Section: численное моделированиеunclassified
“…The last criterion was designed in [12] for linear PDE systems and then generalized in [9] to polynomially nonlinear systems. The computational experiments done in papers [2,3] with the Navier-Stokes equations demonstrated a substantial superiority in numerical behavior of s-consistent schemes over s-inconsistent ones.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we consider the two-dimensional flow of an incompressible fluid described by the following system of partial differential equations (PDEs): Here the velocities u and v, the pressure p, and the external forces f (1) and f (2) are functions in x and y; Re is the Reynolds number and ∆ := ∂ xx + ∂ yy is the Laplace operator. A flow that is governed by these equations is denoted in the literature as a Stokes flow or a creeping flow.…”
Section: Introductionmentioning
confidence: 99%